Retroperitoneal mature cystic teratoma involving the left adrenal gland in a 75-year-old male: a case report and literature review. Issue 11 (24th November 2020) - Tojal, André; Santos, Natália; Vicente, João; Carrilho, Noel; Casimiro, Carlos
Abstract: Primary retroperitoneal teratomas involving adrenal glands are extremely uncommon, particularly in elderly males. Only a few case reports have been documented in the literature so far. We report a mature cystic retroperitoneal teratoma in the region of left adrenal gland in an asymptomatic 75-year-old male patient. It was incidentally found on an abdominal computed tomography scan and was thought to be an adrenal adenoma. Because of its relatively large size and the patient's request, he underwent a laparoscopic left adrenalectomy. Histopathological examination revealed a benign mature cystic retroperitoneal teratoma in the region of the left adrenal gland. The patient had an uneventful postoperative course and is free of recurrence after 20 months of follow-up. Considering the diagnostic difficulty of retroperitoneal teratoma by radiologic imaging, and its risk of malignancy, surgical resection via a minimally invasive approach would be the best diagnostic and therapeutic option. A literature review on teratomas is included.